A Laryngoscope with Shape Memory Actuation - Fischer Nikola; Ho Patty; Marzi Christian; Schuler Patrick; Mathis-Ullrich Franziska (Current Directions in Biomedical Engineering)
Endotracheal intubation is a medical procedure to secure a patient’s airways, which can be challenging in emergency situations due to an individual’s anatomy. Intubation blades can benefit from an adjustable design with shape memory alloys. We present a novel blade design with two degrees of freedom, continuously transforming a straight into a curved blade. Our demonstrators reached mean angular deflections up to 16∘ without exceeding outer blade temperatures of 40∘C. Mean forces of almost 24N were applicable. This approach has the potential to reduce the complexity of intubation procedures and increase the success rate, especially in time-critical emergency situations.